Wali Songo's Teachings as an Inspiration for Education in Preventing Intolerance Among Adolescents - Reidana, Linka Latifany Falasifa; Hambali, Im; Rahman, Diniy Hidayatur; Muslihati, Muslihati (Universitas Islam Negeri Raden Intan Lampung, 2024)
Adolescents are valuable assets for Indonesia's progress, yet many of them face issues such as delinquency and intolerance. This study aims to examine the tolerance values taught by Wali Songo as an inspiration for multicultural guidance and counseling services to prevent intolerance among adolescents. The study employs a Systematic Literature Review (SLR) method with the PRISMA framework to explore Wali Songo's teachings in mitigating intolerance among youth. A total of 89 articles were identified, filtered to 62 relevant ones, and ultimately analyzed 10 high-quality articles. This approach involves multicultural education, social activities, interfaith dialogues, and creative programs emphasizing cooperation and empathy. The findings indicate that applying Wali Songo's tolerance values in guidance and counseling services can shape adolescents to become more inclusive and appreciative of diversity, fostering a more harmonious society.